Behavior of mobile application users of small and medium-sized companies in the city of Tacna - Diaz Zelada, Yvan (2021)
Talking about mobile applications is talking about App. According to what was published by AppBain, on its official site, at the time of writing this article, a total of 3,036,608 mobile applications are counted, only for the Android operating system , of which 16% are considered low quality. And it is that information technologies, added to mobile devices, have become for many companies an opportunity to improve their business processes since they offer a competitive advantage if they are used correctly. But this digital transformation, which has been talked about for some years, has had an impact on the behavior of entrepreneurs, but also on consumer behavior and the way they react to technological trends, taking into account that The App has been incorporated into all business processes of all business sectors, so analyzing a sector such as small and medium-sized companies could give us an overview of what impact the use of App has on the business objectives of SMEs. This study seeks to analyze the behavior of mobile application users of small and medium-sized companies in the city of Tacna and how these have impacted on business decisions in Tacna SMEs, what advantages and disadvantages do these offer for small and medium-sized companies entrepreneurs as well as for consumers.